Impact of NPSR1 gene variation on the neural correlates of phasic and sustained fear in spider phobia: an imaging genetics and independent replication approach - Leehr, Elisabeth Johanna; Brede, Leonie S; Böhnlein, Joscha; Roesmann, Kati; Gathmann, Bettina; Herrmann, Martin J.; Junghöfer, Markus; Schwarzmeier, Hanna; Seeger, Fabian R.; Siminski, Niklas; Straube, Thomas; Klahn, Anna Luisa; et al. (Social cognitive and affective neuroscience, 2024)
The functional neuropeptide S receptor 1 (NPSR1) gene A/T variant (rs324981) is associated with fear processing. We investigated the impact of NPSR1 genotype on fear processing and on symptom reduction following treatment in individuals with spider phobia. A replication approach was applied [discovery sample: Münster (MS) nMS = 104; replication sample Würzburg (WZ) nWZ = 81]. Participants were genotyped for NPSR1 rs324981 [T-allele carriers (risk) versus AA homozygotes (no-risk)]. A sustained and phasic fear paradigm was applied during functional magnetic resonance imaging. A one-session virtual reality exposure treatment was conducted. Change of symptom severity from pre to post treatment and within session fear reduction were assessed. T-allele carriers in the discovery sample displayed lower anterior cingulate cortex (ACC) activation compared to AA homozygotes independent of condition. For sustained fear, this effect was replicated within a small cluster and medium effect size. No association with symptom reduction was found. Within-session fear reduction was negatively associated with ACC activation in T-allele carriers in the discovery sample. NPSR1 rs324981 genotype might be associated with fear processing in the ACC in spider phobia. Interpretation as potential risk-increasing function of the NPSR1 rs324981 T-allele via impaired top-down control of limbic structures remains speculative. Potential association with symptom reduction warrants further research.